2014
DOI: 10.1016/j.vetpar.2014.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular typing of Cryptosporidium in dairy cattle in England and Wales and examination of potential on-farm transmission routes

Abstract: An average of 70 samples were collected from 80 dairy farms in England and Wales, from cattle, co-grazed sheep, wildlife and farm wastes, to investigate prevalence, potential sources and transmission routes of Cryptosporidium. At least one positive sample was detected on 74 of the farms (92.5%) by IFAT microscopy. The prevalence in cattle was 10.2% (95% CI 9.4-11.1%), with greater prevalences detected in calf samples, especially from those under 1 month (45.1%). Young calves were also more likely to be sheddin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
65
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 30 publications
13
65
1
Order By: Relevance
“…Although Cryptosporidium and Giardia infections have been reported for cattle in many parts of the world, prevalence data have often varied markedly. The present detection rate of Cryptosporidium infection based on microscopic examination is much higher compared to the obtained prevalence in former studies in Thailand, Argentina, Ethiopia, England, India and Wales with the prevalence of 0.6, 19.35, 7.8, 12.50 and 10.2 per cent, respectively (Jittapalapong et al, 2006;Tiranti et al, 2011;Wegayehu et al, 2013;Singla et al, 2013;Smith et al, 2014). Similar results with this study, high prevalence rates were also reported in Canada, Germany, Nigeria, Tanzania and Brazil with the prevalence rates of 32, 41.3, 33.0, 35 and 45 per cent, respectively (Budu-Amoako et al, 2012;Gillhuber et al, 2014;Faleke et al, 2014;Swai and Schoonman, 2010;Almeida et al, 2010).…”
Section: Resultscontrasting
confidence: 55%
“…Although Cryptosporidium and Giardia infections have been reported for cattle in many parts of the world, prevalence data have often varied markedly. The present detection rate of Cryptosporidium infection based on microscopic examination is much higher compared to the obtained prevalence in former studies in Thailand, Argentina, Ethiopia, England, India and Wales with the prevalence of 0.6, 19.35, 7.8, 12.50 and 10.2 per cent, respectively (Jittapalapong et al, 2006;Tiranti et al, 2011;Wegayehu et al, 2013;Singla et al, 2013;Smith et al, 2014). Similar results with this study, high prevalence rates were also reported in Canada, Germany, Nigeria, Tanzania and Brazil with the prevalence rates of 32, 41.3, 33.0, 35 and 45 per cent, respectively (Budu-Amoako et al, 2012;Gillhuber et al, 2014;Faleke et al, 2014;Swai and Schoonman, 2010;Almeida et al, 2010).…”
Section: Resultscontrasting
confidence: 55%
“…reported that cryptosporidiosis risk is higher in calves younger than 30 days old (Tiranti et al 2011;Smith et al 2014;Delafosse et al 2015;Avendaño et al 2018).…”
Section: Introductionmentioning
confidence: 98%
“…High herd prevalence of Cryptosporidium spp. has been reported in dairies, with values ranging from 50.5 to 96% (Hamnes et al 2006;Brook et al 2008;Trotz-Williams et al 2008;SilverlĂ„s et al 2009;Tiranti et al 2011;Smith et al 2014;Delafosse et al 2015;Al Mawly et al 2015). It has been Section Editor: Lihua Xiao Electronic supplementary material The online version of this article (https://doi.org/10.1007/s00436-019-06366-y) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated, calf herds with diarrhoea were eight times more likely to be shedding Cryptosporidium and should be considered a human health risk, especially considering Cryptosporidium's low infective dose to people (as few as 30 oocysts or cysts, far less than what a naturally infected calf would excrete into the environment), the relatively high estimated faecal loading potential of a shedding calf and the high survival and resilience of Cryptosporidium oocysts in the environment (DuPont et al 1995;Zambrisky et al 2013;Ryan et al 2014). Further, younger calves have been described as more likely to be infected with and shedding the zoonotic species of Cryptosporidium, C. parvum, (Smith et al 2014). Because younger calves in our study were more likely to have diarrhoea, they may also be more likely to shed zoonotic parasites of public health concern compared to host-specific genotypes like C. andersonii that are more often shed by older animals.…”
Section: Human and Animal Health Risksmentioning
confidence: 72%